The Synthesis of Dendrimer-Based Infection Imaging Probes - Mackey, Victoria (My University, 2013)
Dendrimers provide an ideal scaffold for molecular imaging and therapeutics due to their mono-disperse structure and easily modifiable core, interior, and periphery. The controlled-stepwise synthesis leads to perfect, defined architectures that can easily be modified to incorporate targeting and imaging moieties. Specifically poly (2,2-bis(hydroxymethyl)-propanoic acid) (PMPA) dendrimer structures exhibit excellent aqueous solubility, low toxicity, biocompatibility and biodegradability, which are necessary requirements for an ideal in vivo imaging scaffold.
Fever of unknown origin (FUO) is a common condition involving elevated temperatures above 101°F, which goes undiagnosed after a week of investigation. The primary causes of FUO are infection and cancer, however methods of diagnosis are non-specific and quite slow. Developing a method to detect bacterial infections, and therefore rule out more severe conditions such as cancer, would be very useful in diagnosis of this condition. Approximately two thirds of infection cases in hospitals are determined to be caused by one of six pathogens known as the ESKAPE pathogens and developing a molecular imaging probe that would detect these specific pathogens would be a very useful FUO diagnostic tool.
Siderophores are naturally occurring molecules that exhibit a high affinity for Fe3+, and are effective at entering bacterial cells after complexing iron. In particular, Desferal, a commercially available siderophore used for iron chelation therapy, has been successfully modified, radiolabeled, and studied as an imaging agent. Dendrimers were modified with Desferal and used to investigate the effect of multivalent display of siderophores on a single macromolecular structure.1-3
We herein discuss the preparation of a series of siderophore-terminated PMPA dendrimers that were radiolabeled and studied to compare bacterial uptake between a monomeric siderophore and a macromolecule displaying multiple siderophores on its periphery. To introduce Desferal to the periphery of a dendrimer, activated p-nitrophenyl carbonates were used. A series of Desferal-terminated dendrimers of generations 1-3 was synthesized in yields of 59-89 % and evaluated for suitability as an infection-imaging probe.
The Desferal-terminated dendrimer series was evaluated for its affinity to iron(III) and gallium(III), as well as tested for steric hindrance effects at the periphery. The series was successfully radiolabeled with 67Ga using mild conditions and in vitro bacterial uptake studies were performed with Staphylococcus aureus, one of the ESKAPE pathogens, to determine if multivalency increases bacterial uptake.
Preliminary results indicate that the poor water solubility of the Desferal-terminated dendrimer series needs to be improved in order to increase bacterial uptake of the compounds, however viable candidates for metal chelation were successfully produced.
Keywords: Dendrimers; Infection; Probes; Polymer Chemistry; Polymer Chemistry